Data analytics in football positional data collection, modelling and analysis - Memmert, Daniel; Raabe, Dominik (Routledge, Taylor & Francis Group, 2018)
Data Analytics in Football provides students, researchers and coaches with a firm grounding in the principles of modern performance analysis. It offers an insight into the use of positional data, exploring how it can be collected, modelled, analysed and interpreted. Introducing cutting-edge methods, the book challenges long-held assumptions and encourages a new way of thinking about football analysis.